2014
DOI: 10.1039/c4dt00600c
|View full text |Cite
|
Sign up to set email alerts
|

Tuning coordination modes of pyridine/thioether Schiff base (NNS) ligands to mononuclear manganese carbonyls

Abstract: We have investigated the coordination modes of NNS Schiff base, thioether ligands to manganese (I) carbonyls. The ligands contain ortho substituted pyridines (H, CH 3 , OCH 3 , fluorophenyl) and varying substituents (H, CH 3 ) at the Schiff base linkage. In general, reaction of [Mn(CO) 5 Br] with a tridentate NNS ligand in CH 2 Cl 2 affords species in which the thioether-S may be bound or unbound to the manganese center, depending on the steric and electronic substitution in the ligand framework; as a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Even after halide abstraction with Lewis acids such as AgPF 6 , addition of CF 3 anions was unsuccessful. Moving to a Mn (I) source, (CO) 5 MnBr, allowed for an easy exchange of CO groups with various ligands [39][40][41][42] but displacement of Br with CF 3 again was problematic, even after abstraction with AgPF 6 . While we chose to avoid toxic and difficult to prepare Cd(CF 3 ) 2 , this may offer an alternate route to Mn-CF 3 complexes with soft donors such as phosphines.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Even after halide abstraction with Lewis acids such as AgPF 6 , addition of CF 3 anions was unsuccessful. Moving to a Mn (I) source, (CO) 5 MnBr, allowed for an easy exchange of CO groups with various ligands [39][40][41][42] but displacement of Br with CF 3 again was problematic, even after abstraction with AgPF 6 . While we chose to avoid toxic and difficult to prepare Cd(CF 3 ) 2 , this may offer an alternate route to Mn-CF 3 complexes with soft donors such as phosphines.…”
Section: Resultsmentioning
confidence: 99%
“…Further workup was unnecessary as we found that ligand substitution on the acyl complex was accompanied by rapid decarbonylation at room temperature. Moving to a Mn (I) source, (CO)5MnBr, allowed for an easy exchange of CO groups with various ligands [39][40][41][42]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the properties of such complexes are heavily influenced by the nature of the ligands [10], much attention has been given to the design and synthesis of chelating ligands. Tridentate Schiff base ligands often exhibit versatile chelating modes, such as NNN, NNO, NNS and ONO [11][12][13][14][15][16]. Hence, the design and synthesis of such ligands remains an interesting area of current research.…”
Section: Introductionmentioning
confidence: 99%